Institutional Investors and Firm Valuation: Evidence from Latin America (2015)
This article analyses how the corporate valuation of Latin American firms is affected by the presence of an institutional block holder investor. The study uses a data set of 562 firms from six Latin American countries for the period 1997 to 2011. As in similar studies, we found that the presence of an institutional investor has a positive effect of 8% on firm value. After dividing the sample by investor type, we found that the presence of a grey investor (pension funds and insurance companies) has a negative effect on firm valuation, while independent investors (banks, investment and mutual funds) have a positive effect on firm valuation. This is one of the first studies to evaluate the relationship between investor activism and corporate valuation in Latin American economies with the most significant capital market development.